Analysis of Factors Affecting the Incidence of Hais (Healthcare Associated Infections) in the Inpatient of Dr. Iskak Hospital Tulungagung - Widiastuti Utami; Sentot Imam Suprapto; Indasah (Journal of Community Engagement in Health, 2024)
One of the efforts to prevent and stop the incidence of infection in health care facilities is to break or eliminate the chain of transmission of infection consisting of 6 components (infectious agent, reservoir, portal of exit, transmission method, portal of entry, suscptible host).  Prevention can also be done by observing the risk factors and characteristics of the patient. The purpose of the study was to analyze factors that affect the incidence of HAIs (healthcare associated infections) in the inpatient of RSUD dr Iskak Tulungagung. The research design is in the form of quantitative research with case control analytical observational research methods with a retrospective approach. The research samples were some employees at RSUD dr. Iskak Tulunggung Regency as many as 83 case groups and 83 control groups with sampling techniques using the simple random sampling method. The results showed that the factors that influence the incidence of HAIs at RSUD dr. Iskak Tulungagung is an invasive action, a type of microorganism germ and the length of the day of treatment. While the most dominant factor affects the incidence of HAIs at RSUD dr. Iskak is the length of days of treatment with an OR of 5.256, meaning that the factor of length of days of care is 5 times more influential on the increase in the incidence of HAIs at RSUD dr. Iskak Tulungagung. Providing appropriate prophylactic antibiotics, balanced nutrition and vaccination to patients are steps that must be taken to help the patient's immune system remain in a state of being able to fight infection.